2014
DOI: 10.3390/rs6087379
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Regional Water Mass Variations from GRACE Satellite Gravimetry to Large-Scale Water Management in Africa

Abstract: Time series of regional 2° × 2° Gravity Recovery and Climate Experiment (GRACE) solutions of surface water mass change have been computed over Africa from 2003 to 2012 with a 10-day resolution by using a new regional approach. These regional maps are used to describe and quantify water mass change. The contribution of African hydrology to actual sea level rise is negative and small in magnitude (i.e., −0.1 mm/y of equivalent sea level (ESL)) mainly explained by the water retained in the Zambezi River basin. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 75 publications
3
57
1
Order By: Relevance
“…Significant positive trends can also be found in southern Africa, near the Upper Zambezi and Okavango river basins as well as in the Sahel and the Niger basin, and these trends have already been well documented (Ramillien et al 2014). In a comparison with rainfall observations from different sources, Ahmed et al (2014) have found that the increasing trend in the Niger basin could be related to an increase in precipitation; however, this was not the case for the Upper Zambezi and the Okavango basins.…”
Section: Linear Trendsmentioning
confidence: 83%
See 1 more Smart Citation
“…Significant positive trends can also be found in southern Africa, near the Upper Zambezi and Okavango river basins as well as in the Sahel and the Niger basin, and these trends have already been well documented (Ramillien et al 2014). In a comparison with rainfall observations from different sources, Ahmed et al (2014) have found that the increasing trend in the Niger basin could be related to an increase in precipitation; however, this was not the case for the Upper Zambezi and the Okavango basins.…”
Section: Linear Trendsmentioning
confidence: 83%
“…So far, little attention has been devoted to GRACE variability in this region as most of the signal is contaminated by noise. Nevertheless, these drying trends have been partly documented (Ahmed et al 2014;Ramillien et al 2014) and to some extent attributed to groundwater extraction from fossil aquifers in the Sahara region.…”
Section: Linear Trendsmentioning
confidence: 99%
“…Usually, arid and semi-arid basins have poor rainfall monitoring networks. In our case, MDB has much denser monitoring networks than LEB does; the latter has a large unpopulated region without rainfall stations [63]. At basin scales, the RMSE calculated between BoM and TRMM 3B43 rainfall datasets are 3.0 and 27.4 mm/month for MDB and LEB, respectively.…”
Section: Discussionmentioning
confidence: 86%
“…At basin scales, the RMSE calculated between BoM and TRMM 3B43 rainfall datasets are 3.0 and 27.4 mm/month for MDB and LEB, respectively. By blending gauge records with ancillary rainfall data, such as radar and satellite measurements or an ensemble method, may improve the accuracy of rainfall input data [63,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation